2010
DOI: 10.1016/j.jtcvs.2010.04.043
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastometrically guided transfusion protocol during aortic surgery with circulatory arrest: A prospective, randomized trial

Abstract: Objective: Aortic surgical procedures requiring hypothermic circulatory arrest are associated with altered hemostasis and increased bleeding. In a randomized clinical trial, we evaluated effects of thromboelastometrically guided algorithm on transfusion requirements. Methods: Fifty-six consecutive patients (25 with acute type A dissection) undergoing aortic surgery with hypothermic circulatory arrest were enrolled in a randomized trial during a 6-month period. Patients were randomly allocated to treatment grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
142
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(152 citation statements)
references
References 24 publications
4
142
1
1
Order By: Relevance
“…It has been shown that A5-A15 values (clot firmness 5-15 min after CT) are able to predict MCF within 5-15 min [32]. When the value of FIBTEM-A10 is b8 mm (EXTEM A10 b 45 mm and FIBTEM A10 b 15 mm) or FIBTEM-MCF is b 10 mm, these might be an indication for fibrinogen replacement [17,33,34]. If the effect of heparin is excluded, the prolonged CT values of EXTEM or INTEM (usually EXTEM-CT N 80-100 s or INTEM-CT N 240 s) can suggest that fresh frozen plasma or prothrombin complex concentration transfusion is needed [31].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that A5-A15 values (clot firmness 5-15 min after CT) are able to predict MCF within 5-15 min [32]. When the value of FIBTEM-A10 is b8 mm (EXTEM A10 b 45 mm and FIBTEM A10 b 15 mm) or FIBTEM-MCF is b 10 mm, these might be an indication for fibrinogen replacement [17,33,34]. If the effect of heparin is excluded, the prolonged CT values of EXTEM or INTEM (usually EXTEM-CT N 80-100 s or INTEM-CT N 240 s) can suggest that fresh frozen plasma or prothrombin complex concentration transfusion is needed [31].…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative monitoring of coagulation using rotational thromboelastometry represents a modern approach in perioperative point-of-care testing (POCT) in anesthesia and intensive care [1][2][3]. Thrombelastography (TEG) not only allows for studying clot formation, it also provides information about clot strength and clot lysis.…”
Section: Introductionmentioning
confidence: 99%
“…Rotational thromboelastometry (ROTEM delta; TEM Innovations GmbH, Munich, Germany), based on the classic TEG first introduced by Hartert [4], allows for fast point-of-care blood clot analysis. The ROTEM device was shown to be beneficial in detecting thrombocytopenia, low fibrinogen levels and in guiding substitution therapy with blood products and coagulation factors [3,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…A number of patients with normal PLT, PT and APTT exhibit active bleeding and abnormal coagulation (36,37). Blood coagulation and an increase in PLT adhesion serve roles in the occurrence and development of acute thrombosis (27).…”
Section: Discussionmentioning
confidence: 99%
“…Although D-dimer levels and pAgt can provide reference data for clinical thrombosis, the information provided by TEG detection is more comprehensive and can reflect the coagulation function state more accurately. Furthermore, TEG is a simpler, faster and more sensitive detection method and can be implemented by the bedside (37). …”
Section: Discussionmentioning
confidence: 99%